CircRNA: a novel type of biomarker for cancer - Zhang, He-da; Jiang, Lin-hong; Sun, Da-wei; Hou, Jun-chen; Ji, Zhen-ling (Breast cancer (Tokyo, Japan), 2018)
Circular RNAs (circRNAs) are a class of long, non-coding RNAs molecules that shape a covalently closed continuous loop which have no 5′–3′ polarity and contain no polyA tail. CircRNAs also possess relatively jarless framework and are highly tissue-specific expressed in the eukaryotic transcriptome. Emerging evidences have discovered that thousands of endogenous circRNAs are present in mammalian cells and they mediate gene expression at the transcriptional or post-transcriptional level by binding to microRNAs or other molecules and then inhibit their function. Similarly, increasing evidence indicates that circRNAs may play a role in the development of several types of diseases, including atherosclerotic vascular disease risk, neurological disorders, prion diseases, osteoarthritis and diabetes. Furthermore, circRNAs exhibit aberrant expression in multiform types of cancer, including colorectal cancer, hepatocellular carcinoma and pancreatic ductal adenocarcinoma. And based on the function of circRNAs in cancer, we believe that circRNAs may serve as diagnostic or tumor promising biomarkers. Moreover, it will provide a new therapeutic target for the treatment of cancer.